2023
DOI: 10.1002/pon.6095
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between demoralization and quality of life in end‐of‐life cancer patients

Abstract: Objective To examine the relationship between demoralization and health‐related quality of life (HRQoL) in a sample of end‐of‐life cancer patients with a life expectancy of 4 months or less undergoing palliative care, controlling for sociodemographic, clinical, and psychological variables. Methods Sociodemographic, clinical, and psychological data from 170 end‐of‐life cancer patients were collected using the following scales: Edmonton Symptom Assessment System for palliative care patients' symptoms; Patient He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although the GDS-15 is not a diagnostic instrument, the cut-off score of 5 indicates the presence of depressive symptoms. This demonstrated good internal consistency with a Cronbach's α = 0.94 and good concurrent validity with the (0.84) Zung Self-Rating Depression Scale and (0.83) the Hamilton Depression Rating scale [19]. Several short-item versions of the GDS are also in use.…”
Section: Instrumentsmentioning
confidence: 92%
“…Although the GDS-15 is not a diagnostic instrument, the cut-off score of 5 indicates the presence of depressive symptoms. This demonstrated good internal consistency with a Cronbach's α = 0.94 and good concurrent validity with the (0.84) Zung Self-Rating Depression Scale and (0.83) the Hamilton Depression Rating scale [19]. Several short-item versions of the GDS are also in use.…”
Section: Instrumentsmentioning
confidence: 92%
“…While demoralization and depression share similarities, they are distinct conditions, with demoralization characterized by feelings of subjective incompetence and a lack of hope [15,16]. Studies have shown that demoralization can impact various aspects of a cancer patient's life, including quality of life, sleep quality, spiritual interests, and suicide risk [17][18][19]. Furthermore, demoralization has been linked to factors such as existential anxiety, masculine self-esteem, resilience, and perceived stress, all of which play a role in predicting psychological well-being and the development of depression in cancer patients [20][21][22][23].…”
Section: Exploring the Burden Of Depression In The Cancer Populationmentioning
confidence: 99%
“…By maintaining relationships with others, patients can discover and construct personal meaning and significance that resonates with the entirety of their life narrative. Patients living with advanced cancer need to receive help from others to avoid feeling hopeless or becoming socially isolated, as well as to avoid other forms of suffering such as psychosocial distress and demoralization (Bovero et al 2023b). Indeed, connection with and social support from family members is essential throughout the course of a patient's illness, as being with family members can enhance the patient's sense of dignity, continuing to affirm their active roles within their family system.…”
Section: (25)mentioning
confidence: 99%